Human hypoxic pulmonary vasoconstriction is unaltered by 8 h of preceding isocapnic hyperoxia. Issue 17 (12th September 2017) - Cheng, Hung‐Yuan; Croft, Quentin P. P.; Frise, Matthew C.; Talbot, Nick P.; Petousi, Nayia; Robbins, Peter A.; Dorrington, Keith L.
Abstract: Exposure to sustained hypoxia of 8 h duration increases the sensitivity of the pulmonary vasculature to acute hypoxia, but it is not known whether exposure to sustained hyperoxia affects human pulmonary vascular control. We hypothesized that exposure to 8 h of hyperoxia would diminish the hypoxic pulmonary vasoconstriction (HPV) that occurs in response to a brief exposure to hypoxia. Eleven healthy volunteers were studied in a crossover protocol with randomization of order. Each volunteer was exposed to acute isocapnic hypoxia (end‐tidal P O 2  = 50 mmHg for 10 min) before and after 8 h of hyperoxia (end‐tidal P O 2  = 420 mmHg) or euoxia (end‐tidal P O 2  = 100 mmHg). After at least 3 days, each volunteer returned and was exposed to the other condition. Systolic pulmonary artery pressure (an index of HPV) and cardiac output were measured, using Doppler echocardiography. Eight hours of hyperoxia had no effect on HPV or the response of cardiac output to acute hypoxia. Abstract : Exposure to sustained hypoxia is known to increase the sensitivity of the human pulmonary vasculature to acute hypoxia, but it is currently not known whether exposure to sustained hyperoxia also alters human pulmonary vascular control. We exposed eleven healthy volunteers to acute hypoxia before and after an eight‐hour exposure to hyperoxia. We found no effect of sustained hyperoxia on the pulmonary vascular sensitivity or cardiac output response to acute hypoxia.